2005
DOI: 10.7326/0003-4819-143-3-200508020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Obesity and the Risk for Gastroesophageal Reflux Disease and Its Complications

Abstract: Obesity is associated with a statistically significant increase in the risk for GERD symptoms, erosive esophagitis, and esophageal adenocarcinoma. The risk for these disorders seems to progressively increase with increasing weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

32
674
6
45

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,078 publications
(757 citation statements)
references
References 52 publications
32
674
6
45
Order By: Relevance
“…This association was even more pronounced in males, and after adjustment for potential confounders, such as age, gender, and race, the observed associations of adiponectin with BE remained significant. Obesity is shown to be an independent risk factor of GERD23 through increased transient lower esophageal sphincter relaxation, which is an important mechanism of GERD 24. These results were compatible with our study, which demonstrated that weight and BMI was significantly high in Group III (severe GERD) in comparison to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…This association was even more pronounced in males, and after adjustment for potential confounders, such as age, gender, and race, the observed associations of adiponectin with BE remained significant. Obesity is shown to be an independent risk factor of GERD23 through increased transient lower esophageal sphincter relaxation, which is an important mechanism of GERD 24. These results were compatible with our study, which demonstrated that weight and BMI was significantly high in Group III (severe GERD) in comparison to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In a meta-analysis of nine studies, Hampel, et al noted that obesity is associated with a statistically significant increase in the risk of esophageal adenocarcinoma. The odds ratio for developing EAC was 1.52 (95 % CI 1.147-2.009) for those with a BMI of 25 to 30 kg/ m 2 and increased to 2.78 (95 % CI 1.850-4.164) for those with a BMI greater than 30 kg/m 2 [11]. Similarly, Lanergern et al reported a weight-dependent relation between BMI and EAC and documented that obese persons with a BMI greater than 30 kg/m (2) had the highest risk (OR=16.2, CI 6.3-41.4) [12].…”
Section: Discussionmentioning
confidence: 96%
“…8 High BMI is a risk factor for gastroesophageal reflux disease (GERD) and, consequently, for EAC. [9][10][11] Several studies have reported that high BMI was not associated with improved or reduced overall survival (OS) after esophagectomy, [12][13][14] although increased postoperative morbidity, such as respiratory complications, anastomotic leaks, and length of hospital stay, have been associated with high BMI in patients with gastroesophageal cancer who are undergoing surgery. 14,15 Many of these studies included small number of patients, in whom adjunctive therapy (preoperative chemotherapy and/or radiotherapy) was used.…”
mentioning
confidence: 99%